A new HLA‐B allele, B*18:105, identified in a Caucasian Spanish individual. Issue 2 (February 2015) - Balas, A.; García‐Sánchez, F.; Vicario, J. L.
<x xml:space="preserve">Abstract</x> HLA‐B*18:105 shows two nucleotide differences regarding B*18:22 (97 AGC>AGG, 99 TAC>TAT) and B*18:52 (94 ACC>ATC, 95 CTC>ATC).